Bronchiolitis obliterans in systemic lupus erythematosus: beneficial effect of intravenous cyclophosphamide. Issue 12 (December 1991) - Godeau, B; Cormier, C; Menkes, C J
Abstract : A 49 year old white woman with systemic lupus erythematosus and bronchiolitis obliterans was treated with prednisone (1 mg/kg daily), which led to a transitory improvement in pulmonary status. Cyclophosphamide was then added--4 mg/kg daily intravenously for five days, then 2 mg/kg daily orally--and this was followed by a dramatic and prolonged improvement.